RECONSTRUCTION OF THE AUTHORITY OF THE STATE ADMINISTRATIVE COURT REGARDING THE DETERMINATION OF APPLICATIONS POSITIVE FICTION ( Analysis Critical Post The Birth Constitution Number 6 of 2023 concerning Determination Regulation Government Replacement Constitution Number 2 of 2022 concerning Create Work ) - Hadita, Cynthia (NOMOI Law Review, 2024)
The problem the disappearance authority State Administrative Court in set application submission fictitious positive Post The Birth Constitution Number 6 of 2023 concerning Determination Regulation Government Replacement Constitution Number 2 of 2022 concerning Create Work (UUCK) is necessary done reconstruction and carried out arrangement more carry on in Regulation Government or Regulation President . Method research used that is legal normative with approach critical legal studies . Research result show that if attitude silent official government considered granted then the Fictitious Decision Positive post UUCK will direct implemented by officials government That Alone without need submit application to PTUN matter This impressed deviate judicial power in set application fictitious positive that must be obeyed by Officials Government .